(untitled) (Statistics, Optimization & Information Computing, 2025)
Phonological awareness is among the key variables in early reading and writing. The better the understanding of spoken language, the easier it will be to acquire written language. Moreover, phonological awareness predicts most of the cases of reading disabilities, such as dyslexia. This study investigates the effect of phonological awareness on the literacy skills of young learners by applying machine learning models. The research analyzed data from 606 preschool children aged 61 to 73 months, divided into control and experimental groups across ten educational institutions. Results reveal significant differences in phonological awareness scores favoring the experimental group, with no notable gender differences. Furthermore, the study found a strong positive correlation between phonological awareness and literacy skills, supported by machine learning metrics such as R² values (0.785 for reading and 0.658 for writing). The current research has underlined the efficacy of both phonological awareness interventions and machine learning for educational insight amplification. This study underscores the critical role that phonological awareness plays in the development of literacy, going on to provide actionable insight into ways to improve Arabic early literacy education.